Preparing for future pandemics: Stress tests and wargames - Frank Milne; David J. Longworth (Queen's University, Department of Economics, 2020)
There is an important interdependence between economic, financial and health policy actions. The recent Covid-19 crisis has demonstrated that, apart from the direct economic consequences from illness and death from the virus, the main economic and financial costs have been due to the varying degrees of preventative measures taken by the public, firms, and governments that directly impacted economic and financial activity. This paper proposes the use of regular, combined medical, economic and financial stress tests and wargames in preparing for future pandemics and other major environmental shocks.
Keywords: I18; H12; H51; H84; G21; 330; Covid-19; Government Policy; Wargames; Stress Tests; Banking; Monetary Policy